Action [poems] - Opal, Anthony (punctum books, 2014)
ACTION - as in begin, genesis, motion - is a collection of poems ultimately concerned with form, those lines drawn in the sand that give way to the profanity of the holy, the holiness of the profane. Throughout ACTION, Opal engages the constraints inherent to seemingly fixed forms. From living with rheumatoid arthritis, to feeling for the edges of a sonnet tradition, to wrestling with the tenets of historical theology, this collection demonstrates that the only way to honestly submit to a form is to rage against it. However, to assume that this rage is not a kind of explosive joy-a Barthesian jouissance-would be to miss the point of poems that Dean Young has described as "radiant affirmations of life and art."